The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15251/djnb.2020.151.67
|View full text |Cite
|
Sign up to set email alerts
|

ELECTRICAL AND MAGNETIC PROPERTIES OF BaCoxCd2-xFe16O27 W-TYPE HEXAFERRITES (0 ≤ x ≤ 0.5)

Abstract: A series of W-type Ba-based Co-W ferrites with composition BaCoxCd2-xFe16O27 (x ═ 0.0, 0.1, 0.2, 0.3, 0.4 & 0.5) were fabricated by co-precipitation process at sintering 1100 °C for 8 h. In order to investigate structural, optical, electrical and magnetic properties XRD, FTIR, IV and VSM tools were employed to confirm the formation of ferrites phase. Crystallite size was observed in the range of 71.79 – 27.88 nm with the increase of cobalt contents to confirm the formation of W-type phase. FTIR investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All the samples were dissolved in deionized water to do the UV-Vis spectroscopy. The absorption coefficient of fabricated material was found using the following relation (10) [25].…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…All the samples were dissolved in deionized water to do the UV-Vis spectroscopy. The absorption coefficient of fabricated material was found using the following relation (10) [25].…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…It was observed that the dislocation density was increased with the addition of Zn from 4.06 × 10 -4 nm -2 to 6.46 × 10 -4 nm -2 , as presented in Table 1. The Braggs equation was used to determine the interplanar distance (d), that is given below [10][11][12][13];…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…In order to make a kind of YM based bioink that can be solidified via a photo-crosslinking strategy, appropriate chemical modification was applied to this polysaccharide that make YM crosslinkable by light irradiation [35,36]. Methacryloyl groups were introduced onto the reactive hydroxyl groups of YM to obtain methacryloyl modified YM (YM-MA) by using the method described at 2.2.1.…”
Section: Synthesis and Characterization Of Three Novel Bioinks Derive...mentioning
confidence: 99%